Implementation of Good Corporate Governance towards Productive Zakat Distribution at BAZNAS Kab. Majene (Sharia Economic Review) - Irmawati Irmawati; Darmawati Darmawati; Syahriyah Semaun; Muliati Muliati; Damirah Damirah (Universitas Muhammadiyah Makassar, 2025)
This research analyzes the implementation of Good Corporate Governance towards the distribution of productive zakat in BAZNAS Kab. Majene (Sharia Economic Review). The aim of this research is to determine the productive zakat distribution system, the implementation of Good Corporate Governance and an overview of sharia economics at BAZNAS Kab. Majene. The research method used is a qualitative method. The research results show that (1). Management of productive zakat funds goes through the stages of planning, implementation, control (evaluation), reporting and accountability. Collecting productive zakat funds at BAZNAS BAZNAS Majene Regency is through socialization, forming zakat collection or payments that do not yet use application features to facilitate transactions between Muzakki and zakat Amil so that zakat Amil still use a manual system. (2). BAZNAS Kab. Manjene has implemented the principles of good corporate governance in the distribution of zakat funds. BAZNAS District. Manjene routinely provides open financial reports to the muzakki, divides the organizational structure and assigns tasks according to areas of expertise, zakat distribution is in accordance with the institutions responsible for the muzakki and the needs of the mustahik. (3). Distribution of productive zakat at BAZNAS Kab. In carrying out its duties, Manjene has implemented GCG, carried out its duties honestly, responsibly, disciplined and sincere, these characteristics are a description of the characteristics of tabligh, trust, fatonah and siddiq. The distribution of professional zakat is not fully in accordance with the Qur'an because it is mostly distributed to the poo.